Three-dimensional histological imaging of primate brain and correlation with in vivo medical device images - Julien Dauguet (Revue de Primatologie)
The 3D reconstruction of series of histological slices is an imaging technique that appeared about 25 years ago but that is only starting now to become recognized as an imaging modality per se. Thanks to this technique, it becomes possible to restore the spatial consistency of the brain and to match accurately histological slices with an in vivo medical device image such as an MRI or a PET scan. This is of high interest since it allows direct comparison between the histology, often considered as the gold standard in terms of information, and the same medical devices used in clinical routine to image human patients. Thanks to the similarity of their brain with humans and the disease models widely developed for them, non-human primates are privileged species to benefit from this possibility of 3D analysis and in vivo - post mortem correlation. We present in this article a state of the art review of the main techniques proposed to achieve this original imaging technique, followed by a set of some particularly promising neuroimaging applications.